Understanding and Accepting of Organ Donation Among The Students: A Case Study - Hamdan, Nur Insyirah; Hoque, Mesbahul (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
This study was conducted to identify the level of understanding and accepting organ donation and transplantation among fourth year students in Faculty of Quranic and Sunnah Studies, Universiti Sains Islam Malaysia (USIM). Questionnaire instruments were used in this study through the Google Form application and consisted of several questions on the level of understanding and acceptance of students on organ donation and transplantation. A total of 52 students responded the questionnaire successfully. Collected data were analysed using descriptive statistical quantitative methods. Overall, the results of this study found that the level of understanding and accepting organ donation of fourth year students in faculty of Quranic and Sunnah Studies USIM is at a satisfactory level and some of them aspire to be one of the pledges of organ donors.